Facilitating organizational learning and knowledge management in transnational organizations - Smith, Peter A. C., 1933- (Learning organization, 2006)
The papers explore issues such as the 'learning by doing' capability of the operations function of the trans-national; analysis of inter- and intra-knowledge flow transfers in trans-nationals; strategic variables in knowledge flow transfer and achieving competitive advantage; the effect of 'trust' on knowledge sharing and alternative social capital enablers; how trans-nationals face unique issues that technology can help to alleviate. There is also a review of how a state-owned enterprise with national focus has successfully become a major global player, describing the systemic approach taken,